Rainwater harvesting for augmenting rainfed based agricultural income: A success story - Meena, Gopal Lal; Kumar, Ashok; Ali, Shakir; Meena, H R; Mina, B L; Singh, Charan (Indian Farming, 2022)
The success story demonstrates the impact of soil and water conservation (SWC) technology on farmers’ income. An attempt was made to familiarize the farming community with improved technologies for rehabilitating the degraded land especially ravine land and make them productive along with creating some irrigation facility in rainfed area. Compartmental bunding, levelling and bunding on the downside to collect and store harvested rainwater, were the three implemented SWC technologies in the field of a poor farmer during 2018–19. This helped the farmer get good quality and sufficient fodder production for his animals. Also, the increased income and good quality fodder production directly showed promising results on his cattle which reflected in their productivity, thereby benefitting the farmer immensely.